Dampak Open-Door Policy Terhadap Peristiwa Krisis Diplomatik Tahun 2017 Hingga Keluarnya Dari OPEC Tahun 2018 - Christanti, Naomi Febri; Rosyidin, Mohamad; Alfian, Muhammad Faizal (Journal of International Relations, 2022)
After Sheikh Tamim was elected as Emir in Qatar in 2013, the open-door policy underwent a change. Sheikh Tamim defines open-door policy as a progressive and independent movement. Progressively, Sheikh Tamim strongly criticized the diplomatic crisis in 2017 imposed by the Gulf countries. Then independently, Sheikh Tamim decided Qatar to leave OPEC in 2018. In the Sheikh Tamim era, Qatar will carry out policies that focus on efforts to increase economic income diversification through LNG development and improve Qatar's image in the international scope after the diplomatic crisis in 2017. Furthermore, this research will try to answer the research problem regarding to, "Why did Qatar change its open-door policy in 2017-2018 during the leadership of Sheikh Tamim?". This study aims to explain how Sheikh Tamim's background, ideas and beliefs influenced the change in open-door policy and its application in the diplomatic crisis until its withdrawal from OPEC in 2018. This research uses a desk research method with an explanative type. This study uses a leader driven change framework to see how changes in foreign policy are influenced by leaders who have the authority to determine a policy.